Analysis of Competitiveness Improvement of Honey Home Industry in Pangkalan Kerinci - Arista, Syaidini; Ekwarso, Hendro; Zuryani, Hilmah (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study aims to evaluate the internal and external conditions of the honey home industry in Pangkalan Kerinci with the aim of improving its competitiveness. The data collection method used is a census involving 11 respondents who are honey home industry owners. The data used includes primary and secondary data. In analyzing the data, the Porter's Diamond Model and SWOT Analysis methods were used. The results of the analysis using Porter's Diamond Model in the SWOT framework show that the honey home industry in Pangkalan Kerinci is in quadrant 1 (Aggressive strategy). The results of the SWOT diagram also indicate that the honey home industry in Pangkalan Kerinci has a strategy to improve its competitiveness in the internal and external environment. This aggressive strategy focuses more on Strength-Opportunities, by optimizing the strengths possessed to take advantage of existing opportunities.